2012
DOI: 10.4318/tjg.2012.0443
|View full text |Cite
|
Sign up to set email alerts
|

A case of endoscopic ultrasound diagnosis of gastric amyloidosis

et al.

Abstract: Amyloidosis is among a group of diseases caused by a variety of amyloid deposition in the interstitial space that causes damage to cells and organ function, affecting the heart, kidneys, gastrointestinal tract, skin, nervous system, and others. The digestive system is one of the most common encroachment sites of amyloidosis, and it was reported that the gastrointestinal tract was affected in approximately 50-70% of cases (1,2). However, amyloidosis that is limited only to the stomach is rare, and might be pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…A study concluded that Hp positivity could cause symptoms that could explain the inefficacy of colchicine in patients with a diagnosis of FMF and high CRP values 23 . In the literature, it was reported that there is basal inflammation in the non-attack period in patients with a diagnosis of FMF 4,6,19,20 . Observing higher CRP and hs-CRP values in patients with FMF in our study supports this state.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…A study concluded that Hp positivity could cause symptoms that could explain the inefficacy of colchicine in patients with a diagnosis of FMF and high CRP values 23 . In the literature, it was reported that there is basal inflammation in the non-attack period in patients with a diagnosis of FMF 4,6,19,20 . Observing higher CRP and hs-CRP values in patients with FMF in our study supports this state.…”
Section: Discussionsupporting
confidence: 86%
“…23 In the literature, it was reported that there is basal inflammation in the nonattack period in patients with a diagnosis of FMF. 4,6,19,20 Observing higher CRP and hs-CRP values in patients with FMF in our study supports this state.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations